The Last Play: A transmedia installation - Polydorou, Doros (My University, 2022)
This paper focuses on the methodology undertaken, and the lessons learned, to create the location-based, Virtual Reality (VR) story-telling experience. The last play was initially staged in Limassol at a student exhibition show in May 2021 and then again in September 2021 at the Animatikkon Fes-tival in Pafos. The installation is for two people and takes place in two different sections, one physical and one virtual, and it can be experienced in either order. The experience aims to immerse and engage the users by utilizing mecha-nisms borrowed by immersive theatre and game-design such as spatial storytelling, agency, engaging multiple senses and telling the story through multiple mediums. The integration of these various practices seems to be an important element that complements the immersive qualities of the VR experi-ence. Furthermore, the spatial storytelling methodology, the transmedia approach, and the integration of the various physical objects into the experience seem to positively con-tribute to the storytelling aspect of location-based VR instal-lations.
Keywords: Virtual Reality; Story-telling